2020
DOI: 10.3390/v12020147
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Assessment of the Status and Risk of Mosquito-borne Arboviral Transmission in Ghana

Abstract: Entomological surveillance is one of the tools used in monitoring and controlling vector-borne diseases. However, the use of entomological surveillance for arboviral infection vector control is often dependent on finding infected individuals. Although this method may suffice in highly endemic areas, it is not as effective in controlling the spread of diseases in low endemic and non-endemic areas. In this study, we examined the efficiency of using entomological markers to assess the status and risk of arbovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…This putative novel virus was named Aedes permutotetra-like virus 2 (APLV2) ( Figure 3 b). The cluster formed by APLV-1, Culex Daeseongdong-like, Daeseongdong virus 2 and Smothfield permutotetra-like virus have been found in mosquitoes ( Figure 3 c) [ 3 , 28 ]; similarly, the clade formed by APLV-2, Culex permutotetra virus, Shinobi tetravirus and Sarawak virus have also been detected in different mosquito species ( Figure 3 d) [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This putative novel virus was named Aedes permutotetra-like virus 2 (APLV2) ( Figure 3 b). The cluster formed by APLV-1, Culex Daeseongdong-like, Daeseongdong virus 2 and Smothfield permutotetra-like virus have been found in mosquitoes ( Figure 3 c) [ 3 , 28 ]; similarly, the clade formed by APLV-2, Culex permutotetra virus, Shinobi tetravirus and Sarawak virus have also been detected in different mosquito species ( Figure 3 d) [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aedes aegypti larvae were collected from four locations in Ghana in 2016 [ 18 ] (Table 1 ). Collection sites included artificial containers in domestic areas of rural villages, which are tourist attraction sites, as well as used tyres in urban, semi-urban, and rural villages (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, similar studies have not yet been conducted in West African countries such as Ghana, with no reported DENV outbreaks, despite an abundance of the Ae. aegypti vector [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations